Effects of educational material among children with clubfoot during bracing stage of treatment by Ponseti method - Ali, Ershad; Hossain, Md Monir; Mohoshina, Marzana; Islam, Rafiqul; Ahammed, Tuhin; Ahad, Wakil (Edorium Journal of Disability and Rehabilitation, 2024)
Aims: To identify effects of educational material among children with clubfoot during bracing stage of treatment by Ponseti method. Methods: This study was a quantitative type quasi-experimental research design. Actually, it was an experiment among specific groups and usual groups. Exercises applied with educational material to the material group or experiment group and only usual exercises applied to the non-material group or the control group. A pre-test (before exercises provided by educational material) and post-test (after exercises provided by educational material) was administered with each subject of both groups to compare the effects on children with clubfoot during bracing stage of treatment by Ponseti method. Results: The mean Pirani score before providing exercises with educational material for right feet among the clubfoot babies were 0.56 ± 0.33 (material group) and after providing exercises with educational material for right feet among the clubfoot babies were 0.43 ± 0.41 (material group). Statistically it was found highly significant (t = 2.99, p greater 0.0003). So, it was concluded that exercises with educational material had significant influence on Pirani score reduction for right feet among the clubfoot babies. The mean Pirani score before providing usual exercises for left feet among the clubfoot babies were 0.5 ± 0.15 (non-material group) and after providing usual exercises for left feet among the clubfoot babies were 0.53 ± 0.48 (non-material group). Statistically it was found significant (t = –0.059, p greater 0.056). So, it was concluded that usual exercises without educational material had influence on Pirani score increased for left feet among the clubfoot babies. Conclusion: The modern treatment of clubfoot is Ponseti method which is very effective, outcome oriented, and less invasive surgical procedure. This study was concluded that exercises with educational material had significant influence on Pirani score reduction among the children with club foot. So, there was significant importance of exercises with educational material rather than usual exercises by verbal instructions.